BIODIGESTOR DE DOBLE PROPOSITO - PRODUCCIÓN E INVESTIGACIÓN - PARA RESIDUOS DE GRANJA PORCÍCOLA - Acevedo, P. (Revista ION, 2010)
Here is, with some detail, the design and operation of a Biodigester for the treatment of the remainders in a pig farm where biogas is produced for cooking human and animal food in an integral farm. Also liquid fertiiizer is produced and used in agricultural labours and for the growing of grass while some of the solids by-products are destined to feed fish; in this front, in addition to biodigester the proposed system is part of a system of integral handling of remainders that turns polluting currents flows of goods and services with economic and environmental valué. Another intention of the designed and instalied biodigester is to aílow investigations of diverse type, as for example oriented to optimize the operation of the system or to optimize the design of improved models. The designed, constructed system is described and in productive operation.